Green‐lighting green fluorescent protein: Faster and more efficient folding by eliminating a cis–trans peptide isomerization event. (30th January 2014) - Rosenman, David J.; Huang, Yao‐ming; Xia, Ke; Fraser, Keith; Jones, Victoria E.; Lamberson, Colleen M.; Van Roey, Patrick; Colón, Wilfredo; Bystroff, Christopher
Abstract: Wild‐type green fluorescent protein (GFP) folds on a time scale of minutes. The slow step in folding is a cis–trans peptide bond isomerization. The only conserved cis ‐peptide bond in the native GFP structure, at P89, was remodeled by the insertion of two residues, followed by iterative energy minimization and side chain design. The engineered GFP was synthesized and found to fold faster and more efficiently than its template protein, recovering 50% more of its fluorescence upon refolding. The slow phase of folding is faster and smaller in amplitude, and hysteresis in refolding has been eliminated. The elimination of a previously reported kinetically trapped state in refolding suggests that X‐P89 is trans in the trapped state. A 2.55 Å resolution crystal structure revealed that the new variant contains only trans ‐peptide bonds, as designed. This is the first instance of a computationally remodeled fluorescent protein that folds faster and more efficiently than wild type.